Advanced techniques for performing photodynamic therapy in deep-seated tissues. (December 2022) - Sun, Bowen; Bte Rahmat, Juwita Norasmara; Zhang, Yong
Abstract: Photodynamic therapy (PDT) is a promising localized cancer treatment modality. It has been used successfully to treat a range of dermatological conditions with comparable efficacy to conventional treatments. However, some drawbacks limit the clinical utility of PDT in treating deep-seated tumors. Notably, the penetration limitation of UV and visible light, commonly applied to activate photosensitizers, makes PDT incompetent in treating deep-seated tumors. Development in light delivery technologies, especially fiber optics, led to improved clinical strategies for accessing deep tissues for irradiation. However, PDT efficacy issues remained partly due to light penetration limitations. In this review, we first summarized the current PDT applications for deep-seated tumor treatment. Then, the most recent progress in advanced techniques to overcome the light penetration limitation in PDT, including using functional nanomaterials that can either self-illuminate or be activated by near-infrared (NIR) light and X-rays as transducers, and implantable light delivery devices were discussed. Finally, current challenges and future opportunities of these technologies were discussed, which we hope may inspire the development of more effective techniques to enhance PDT efficacy against deep-seated tumors.